Aplicación de un biorremediador bacteria em en cultivo de tilapia roja oreochromis sp - Pillajo Calle, Diego Armando (2011)
This research was conducted in the Province of El Oro, Canton Santa Rosa, Finca Los Cherry, via Puerto Jeli, owned by Mr. Jorge Boats, which I made available four ponds of tilapia and their respective infrastructure. As mentioned in the subject our purpose was to discover what changes occur in tilapia culture, both in animals and in soil, with the application of a biorremadiador. This work was based on four objectives: 1.-Establish the bi-weight growth and tilapia from the use of bioremediator 2.-To determine the percentage of survival with the use of bioremediator. 3.-evaluate the changes that occur in the soil by the use of bioremediator in tilapia culture. 4.-Derterminación feed conversion. The duration of the investigation was four months from juvenile, pre-breeding, in the months from May 2010 through August 2010, considerable time to test this work. With respect to the results in animal no morphological changes in weight and length in survival was achieved margin percentage of 92% considered very good on the ground changes were small and in terms of feed conversion good.